Intra-industry trade in Malaysian manufacturing sector - Jambol, Abu Bakar; Ismail, Normaz Wana (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2013)
As a result of rapid economic growth and increased influence of globalization in international trade activities, intra-industry trade (IIT) becomes prominent across Asia including Malaysia. Free trade agreements and creations of free trade areas have encourage increased cross border investments through production networking as well as fragmentation of production, especially in manufacturing sector. This paper attempts to examine trends and patterns of Malaysia’s IIT in manufacturing sector using the 9-digit Standard International Trade Classification (SITC) codes from 1990-2010. The IIT trends and patterns are investigated using the Grubel Lloyd (GL) Index adapted from Greenaway et. al (1995) and Fontagne and Freudenberg (1997). The result indicates that the trends and patterns of Malaysia’s manufacturing sector had gradually migrated from traditional inter-industry to intra-industry kind of trade. The average GL index of Malaysia’s manufacturing sector had been gradually increasing from a mere 0.27 in 1990 to 0.51 in 2007 before it slightly dropped to 0.46 in 2010. In terms of quality (high quality vertical IIT), the composition of Malaysia’s IIT in manufacturing sector had slightly increased from only 28.0% in 1990 to 31.5% in 2010 against other two types of IIT namely horizontal IIT and low quality IIT. Many factors contributed to changes in the trends and patterns in Malaysia’s IIT over the last 2 decades. Apart from import substitution and industrialization policies implemented by the government, increased international fragmentation of production, production networks, creation of ASEAN Free Trade Area (AFTA) and other regional trade agreements are the dominant factors that influenced IIT in Malaysia’s manufacturing activities.